Measurement of specific organ domains in lupus randomized controlled trials: a scoping review. (19th October 2021) - Connelly, Kathryn; Vettivel, Jeevan; Golder, Vera; Kandane-Rathnayake, Rangi; Morand, Eric F
Abstract: Objective: Randomized controlled trials (RCTs) in SLE (lupus) typically adopt composite responder definitions as primary efficacy endpoints; however, outcomes within individual organ domains are also important to understand. The aim of this scoping review was to evaluate how organ-specific disease activity and therapeutic responses have been measured and reported in lupus RCTs. Methods: We searched MEDLINE, EMBASE, Cochrane registry and clinicaltrials.gov. Eligible studies were RCTs investigating efficacy of an immune-directed drug therapy in active SLE, published January 2000–March 2021, excluding studies limited to lupus nephritis. Data were extracted independently in duplicate into a template and summarized descriptively. Results: Thirty-four RCTs were included, of which 32 (94%) reported activity and/or responses in at least one organ domain. Study populations had a high, although variable, frequency of baseline musculoskeletal and mucocutaneous activity and low, but also variable, representation of other domains. Definitions of organ-specific responses were inconsistent, even within individual instruments. Response in most organ domains were evaluated using BILAG and SLEDAI components but meaningful comparison between treatment arms was limited by small subgroups analysed in a post hoc fashion. Specific mucocutaneous and arthritis instruments were also used, including within pre-specified organ-specific endpoints, which discriminated between treatment arms in some studies. Conclusion: Mucocutaneous and musculoskeletal manifestations predominate in SLE RCTs. Organ-specific outcome measures are commonly reported, but definitions of involvement and response are inconsistent. Research into the development of new outcome measures for key organ domains, and validation and comparison of response definitions using existing instruments, is needed.